Drained behaviour of suction caisson foundations on very dense sand - Byrne, B; Houlsby, G (1999)
Alternatives to piled foundations, such as suction caissons, are becoming increasingly viable options for fixed platforms, particularly in the development of marginal fields. Whilst pile design procedures evolved smoothly from onshore experience and theory, design of shallow foundation systems has had to be re-examined in light of the intense offshore loading conditions. This is currently being undertaken through experimental investigations, which indicate the possibility of defining foundation response using plasticity theory. This paper reports the response of circular foundations on very dense sand within the context of plasticity theory. The load and displacement paths are applied using a sophisticated three degree-of-freedom loading rig, designed specifically to explore plasticity related concepts. The tests are on dry sand to ensure drained behaviour. Eight tests are performed on each sand sample, thus minimizing material variations between tests, which is particularly important at the high peak friction angles being explored. The tests were at 1-g, and concentrate on four embedment ratios (0, 0.16, 0.33 and 0.66) on a sand of 95% relative density. The research indicates a change in shape of a yield surface with increase in embedment ratio. Whilst the tests concentrate primarily on the plastic deformations, the behaviour within the yield surface is also examined. A conceptual model, based on plasticity, is presented. The findings of the research are particularly relevant to the offshore industry in the development of shallow and skirted foundations for dense sand deposits.